The investigation of vibro-isolating features of transmissions of vehicles in elastic centrifugal couplings using the method of identification of dynamic processes in half-couplings on the universal dynamic test stand - Spruogis, Bronislovas; Zubavičius, Leonas (Transport, 2002)
The presented paper describes the investigation of vibro-isolating features of transmissions of vehicles using universal dynamic test stand. The stand is protected by copyright and distinguishes itself for many advantages in comparison with the existing stands: it is contactless, precise in a wide frequency range, power-saving, high-speed. Due to low exploitation expenses and wide possibilities it is fit for the investigation of dynamic characteristics of various vehicles. On the said stand using the method of the identification of experiment dynamic processes, the investigation of vibroisolating features of rotor systems has been performed. The errors caused by the unevenness of rotation of connecting shafts, the adequacy of the calculated models and the dangerous resonance frequencies have been determined. First Published Online: 19 Dec 2011